PENGARUH SENAM DIABETIK DENGAN BOLA TENIS TERHADAP TINGKAT SENSITIVITAS KAKI PASIEN DM TIPE II - Muhammad Setiawan; ratanto ratanto; diah setiani (MNJ (Mahakam Nursing Journal), 2019)
Introduction:In 2016, Diabetes Mellitus disease was the third largest disease in Kutai Kartanegara amount 5,266 peoples. DM’s patients have 5 times greater risk of experiencing Diabetic Foot Ulcer. Approximately 15% of DM’s patients experience complications of Diabetic Foot Ulcer due to decreased sensitivity to the feet. Methods: The design of research was quasi experiment by using pre and post test nonequivalent with control group. A sample of 24 respondents were divided into intervention and control groups. The research instrument used Monofilament 10g in both groups to measure the sensitivity of the respondent's feet. Diabetic gymnastics with tennis balls was given to the intervention four times a week. Results: Paired T-Test test show right and left foot p value = 0,000 <0.05 which means there was an influence of diabetic gymnastics with tennis ball against foot sensitivity level in the intervention group. The result of hypothesis test of Independent T-Test showed p value = 0,000 <0,05, which concluded that there was a significant difference between the difference of sensitivity level of right and left foot in both groups. Conclusion: Diabetic gymnastics with tennis ball has an influence on the sensitivity level of DM type II patient. Suggestion: The next researcher is expected to compare between diabetic gymnastics and with other physical exercises as well as using other modifications.